CARICOM : our Caribbean Community : an introduction (Ian Randle Pub. KingstonJM, 2005)
Records the history of and major developments in the Caricom integration movement. Traces key developments that led to the establishment of CARIFTA , later CARICOM, and the initiatives that are being taken to strengthen the Community, most notably the CARICOM Single Market and Economy (CSME). Details the structure and functioning of the Community. Highlights issues and initiatives on which the Community has focused over time, as well as, the major subjects on its current agenda, explaining their actual and potential impact on the Caribbean people. Looks at future challenges.
Bibliography: p. 474-505